Pencirian Genetik Pepper Yellow Leaf Curl Virus pada Tanaman Cabai Merah (Capsicum annuum) di Bengkulu - Sipriyadi Sipriyadi; Abe Novan Aditya Rahman; Welly Darwis Welly Darwis; Risky Hadi Wibowo; Mimi Sutrawati; Cindy Margaret Hutasoit; Yuni Kristina; Redo Setiawan (Institut Pertanian Bogor, 2022)
Chili is one of the horticultural commodities with increasing demand yearly. Rejang Lebong and Kepahiang regencies are the most significant chili-producing areas in Bengkulu. One of the crucial viruses in chili plants is Pepper yellow leaf curl virus (PYLCV). PYLCV virus infection in the vegetative phase can cause stunted plants and fail to bear fruit. This study aims to detect and genetically characterize PYLCV. Samples of chili plants were taken in these two districts using the purposive sampling method. Virus detection was carried out at the Genetics and Biotechnology Laboratory, Department of Biology. Extraction of viral DNA using the Cetyl Trimethyl Ammonium Bromide (CTAB) method. Rep and Trap gene amplification using universal primers of Bemovirus. SPG1 and SPG2. The PCR product was visualized on a 1.2% agarose gel in TAE.. Furthermore, the PCR products were sequenced in PT Genetics Science Indonesia. Virus gene sequences were aligned using Bioedit and MEGA X software. The results showed that of the 24 chili plants sampled in the study, 21 samples showed an amplicon with a size of 900 bp, which follows the length of the amplicon based on the primer used. Of the 21 amplicon results, 6 of them were sequenced and genetically characterized. The results of the genetic characterization of the 6 samples showed the presence of 552 conservative sites (C) (75.6%), 178 variation sites (Vi) (24.4%), parsimony sites (Pi) (15.9%), and 70 singleton (S) sites (8.5%). The highest nucleotide base composition was thymine (T) with an average value of 30.1%, and the lowest was guanine (G) 21.9%, while the highest nucleotide combined composition was AT with an average value of 55%, the lowest was GC approximately 45%. The average genetic distance between samples was 0.13 (13%). Based on the phylogenetic tree, 6 samples were divided into two groups. Keywords: begomovirus, Bengkulu, Capsicum annuum